2016
DOI: 10.1093/molbev/msw143
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Ah Receptor Ligand Selectivity during Hominin Evolution

Abstract: We have identified a fixed nonsynonymous sequence difference between humans (Val381; derived variant) and Neandertals (Ala381; ancestral variant) in the ligand-binding domain of the aryl hydrocarbon receptor (AHR) gene. In an exome sequence analysis of four Neandertal and Denisovan individuals compared with nine modern humans, there are only 90 total nucleotide sites genome-wide for which archaic hominins are fixed for the ancestral nonsynonymous variant and the modern humans are fixed for the derived variant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 53 publications
1
79
0
1
Order By: Relevance
“…Hubbard et al () showed that the AhR variant in modern humans contains Val381 residue in the ligand‐binding domain, while the AhR of Neanderthals, and a Denisovan individual, as well as nonhuman primates and other vertebrates (rodents) encode the ancestral Ala381 variant. The Val381 variant is fixed in the genome of all modern humans as well as in the genome of the oldest (45 ka) AMH individual sequenced to date (Fu et al, ).…”
Section: The Role Of the Ahrmentioning
confidence: 99%
“…Hubbard et al () showed that the AhR variant in modern humans contains Val381 residue in the ligand‐binding domain, while the AhR of Neanderthals, and a Denisovan individual, as well as nonhuman primates and other vertebrates (rodents) encode the ancestral Ala381 variant. The Val381 variant is fixed in the genome of all modern humans as well as in the genome of the oldest (45 ka) AMH individual sequenced to date (Fu et al, ).…”
Section: The Role Of the Ahrmentioning
confidence: 99%
“…Despite the evolutionary conservation of AHR expression from invertebrates to mammals, the gene encoding AHR has undergone functionally significant divergence across and within species [5557]. Evidence highlights a marked variability regarding the potential for a given ligand to induce AHR activity across different species e.g.…”
Section: Inter-species Variability and Intrinsic Ahr Ligandsmentioning
confidence: 99%
“…In this context an interesting divergent ligand selectivity during hominin development has been discovered. Modern humans (in contrast to Neanderthals, other hominins and primates) express the AHR Val381 variant, leading to less sensitivity to aryl hydrocarbon bioactivation but retaining the sensitivity to endogenous indole AHR agonists generated through the IDO1-AHR axis (Hubbard et al, 2016). (2) AHR functions in homeostasis of stem/progenitor cells.…”
Section: Resultsmentioning
confidence: 99%
“…The AHR variant Val381 in modern humans leads to reduced AHR affinity to aryl hydrocarbons in comparison with Neanderthals, (Hubbard et al, 2016). Binding of the photoaffinity ligand 2-azido-3-([ 125 J]iodo-7,8-dibromodibenzo-p-dioxin was much lower; CYP1A1 induction by BaP was reduced in humans carrying the Val381 variant whereas CYP1A1 induction by endogenous ligands such as indirubin and indole was unimpaired.…”
Section: Bioactivation Of Aryl Hydrocarbonsmentioning
confidence: 99%